The systematic search for z ≳ 5 active galactic nuclei in the Chandra Deep Field South. Issue 4 (10th March 2015) - Weigel, Anna K.; Schawinski, Kevin; Treister, Ezequiel; Urry, C. Megan; Koss, Michael; Trakhtenbrot, Benny
Abstract : We investigate early black hole (BH) growth through the methodical search for z ≳ 5 active galactic nuclei (AGN) in the Chandra Deep Field South. We base our search on the Chandra 4-Ms data with flux limits of 9.1 × 10 −18 (soft, 0.5–2 keV) and 5.5 × 10 −17 erg s −1 cm −2 (hard, 2–8 keV). At z ∼ 5, this corresponds to luminosities as low as ∼10 42 (∼10 43 ) erg s −1 in the soft (hard) band and should allow us to detect Compton-thin AGN with M BH > 10 7 M⊙ and Eddington ratios >0.1. Our field (0.03 deg 2 ) contains over 600 z ∼ 5 Lyman Break Galaxies. Based on lower redshift relations, we would expect ∼20 of them to host AGN. After combining the Chandra data with Great Observatories Origins Deep Survey (GOODS)/Advanced Camera for Surveys (ACS), CANDELS/Wide Field Camera 3 and Spitzer /Infrared Array Camera data, the sample consists of 58 high-redshift candidates. We run a photometric redshift code, stack the GOODS/ACS data, apply colour criteria and the Lyman Break Technique and use the X-ray Hardness Ratio. We combine our tests and using additional data find that all sources are most likely at low redshift. We also find five X-ray sources without a counterpart in the optical or infrared which might be spurious detections. We conclude that our field does not contain any convincing z ≳ 5 AGN. Explanations for this result include a low BH occupation fraction, a low AGN fraction, short, super-Eddington growth modes, BH growth through BH–BH mergers or in optically faint galaxies. By searching for z ≳ 5 AGN, we are setting the foundation for constraining early BH growth and seed formation scenarios.